Nonprofit resilience building in turbulent times: towards a process model - Aureliu Sindila; Xueyong Zhan; Yong Jin (Global Public Policy and Governance, 2026)
Abstract Amid weakening institutional environments, fiscal retrenchment, and rising demand for social services, nonprofit organizations (NPOs) worldwide face a fundamental challenge of how to build resilience in their organizations without compromising mission accountability. This article introduces a process model of NPO resilience built around three stages: anticipation, coping, and adaptation. Moving beyond the dominant outcome- and capability-based accounts that have characterized the literature to date, this model specifies how three mechanisms drive this process: (1) accumulating slack resources for shock absorption and experimentation, (2) exercising entrepreneurial judgment for calibrating risk under uncertainty, and (3) empowering frontline responsiveness through dynamic delegation. Crucially, the article situates these mechanisms within broader public policy and governance contexts. Drawing on empirical insights from diverse organizations and institutions, we identify key policy enablers: funding rules that allow the financing of operating reserves, trust-based contracting that balances managerial discretion with oversight, and capacity-building investment in data systems. As part of this process model, we reframe “mission drift” as adaptive mission respecification, arguing that, with clear governance guardrails, strategic pivots preserve rather than erode social value. This study provides a comprehensive roadmap for nonprofit leaders, policy makers, and funders seeking to build nonprofit resilience in turbulent environments.